2023
DOI: 10.1186/s12889-023-15319-1
|View full text |Cite
|
Sign up to set email alerts
|

The impact of high-risk lifestyle factors on all-cause mortality in the US non-communicable disease population

Abstract: Background Previous studies have suggested that lifestyle factors are associated with mortality in different population. However, little is known about the impact of lifestyle factors on all-cause mortality in non-communicable disease (NCD) population. Methods This study included 10,111 NCD patients from the National Health Interview Survey. The potential high-risk lifestyle factors were defined as smoking, excessive drinking, abnormal body mass in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 34 publications
0
9
0
Order By: Relevance
“…It has been demonstrated that the leading causes of morbidity and death today are related to unhealthy lifestyles and chronic stress 21 , 22 . The fact that to make and to motivate a decision (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…It has been demonstrated that the leading causes of morbidity and death today are related to unhealthy lifestyles and chronic stress 21 , 22 . The fact that to make and to motivate a decision (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Tobacco and alcohol use have reciprocal influences on potentiating cravings and interact with each other leading to more frequent use and higher consumption levels [41]. A recent US study has shown that high-risk lifestyle factors tend to cluster in the population and that the joint risk is much higher than the sum of the individual risks [42], highlighting the importance of paying attention to their unhealthy co-effects. The present study confirms that unhealthy lifestyle factors tend to cluster together, as smokers were more frequent alcohol drinkers and had more sedentary habits.…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, eHealth literacy has been shown to positively correlate with health-promoting behaviors (eg, physical activity) and negatively correlate with risk behaviors (eg, sedentary behavior) among young and older adults [ 38 , 39 ]. Therefore, this study would investigate the predictive validity of the eHLS-Web3.0 for 2 specific health behaviors (ie, physical activity and sedentary behavior), given their crucial impact on the physical and mental well-being of older adults with NCDs [ 40 ]. By identifying the predictive validity of the eHLS-Web3.0, this study is expected to make a noteworthy contribution to future research in this field.…”
Section: Introductionmentioning
confidence: 99%